HISTORICAL AND ETYMOLOGICAL ANALYSIS OF THE NAME OF THE CONCEPT STUDENT - V. S. Novikova (Вестник Кемеровского государственного университета, 2014)
The paper examines the word-name of the concept STUDENT in diachronic aspect. On the basis of etymological, explanatory and word-formative dictionaries of the English language the changes in the lexical and semantic structure of this word as well as the formation of new lexemes/sememes in the conceptual field STUDENT are analyzed.